Dataset: Uncovering Trends in Digital Forensics and Criminal Law Research: A Decade of Insights - Rizky Hamdani; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This data article explores the landscape of digital forensics and criminal law research from 2012 to 2022 by analyzing scholarly works available on Lens.org. By applying various filters such as release year, document type, and field of study, we identified 23 relevant journal articles. The analysis revealed insights into the most active institutions, authors, and publishers in the field, as well as the most prolific countries/regions. These findings offer a valuable resource for researchers, policymakers, and practitioners interested in digital forensics and criminal law. Highlights: A decade-long analysis of digital forensics and criminal law research from 2012 to 2022. Identification of the most active institutions, authors, publishers, and countries/regions in the field. Valuable insights for researchers and practitioners interested in digital forensics and criminal law.